2021
DOI: 10.1002/ams2.631
|View full text |Cite
|
Sign up to set email alerts
|

Head positioning in suspected patients with acute stroke from prehospital to emergency department settings: a systematic review and meta‐analysis

Abstract: Aim This study aimed to clarify whether the lying‐flat position from prehospital to emergency department settings more effectively improves neurological outcomes of patients suspected with acute stroke over the sitting‐up position. Methods We searched PubMed, the Cochrane Central Register of Controlled Trials, and Igaku Chuo Zasshi for published randomized controlled trials until September 2019. The study population included patients suspected with acute stroke from pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…In this study, the blood gas analysis results were significantly higher in the intervention group from the 24 hours postoperatively, when the position of the patient showed its first effect. This finding is consistent with the literature 9,12,14,15 . In a study investigating the effect of postoperative lateral position on blood gas parameters in the surgical ICU setting, it was shown that the lateral position improved oxygenation 16 .…”
Section: Discussionsupporting
confidence: 94%
“…In this study, the blood gas analysis results were significantly higher in the intervention group from the 24 hours postoperatively, when the position of the patient showed its first effect. This finding is consistent with the literature 9,12,14,15 . In a study investigating the effect of postoperative lateral position on blood gas parameters in the surgical ICU setting, it was shown that the lateral position improved oxygenation 16 .…”
Section: Discussionsupporting
confidence: 94%
“…There are several differences between the current study and prior studies. First, the head position at −20° was adopted in the current study, while a horizontal supine versus sitting position was utilized in prior studies 2 5 , 8 , 9 , 20 . In theory, HDP can enhance cerebral blood flow and increase cerebral perfusion compared with a supine or sitting position due to the force of gravity 22 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is a paucity of effective neuroprotective treatments for acute ischemic stroke (AIS), other than reperfusion therapy such as intravenous thrombolysis and mechanical thrombectomy, which is limited by a strict therapeutic time window and requirement for a highly developed stroke system of care 1 . The effect of head position (lying-flat vs sitting-up position) as a nonpharmacological therapy on stroke has been investigated 2 5 , but the inconsistent results have led to current ambiguous guideline recommendations 1 6 . It is generally accepted that the supine position may increase blood flow and improve oxygenation 2 4 , 7 9 , but with potential risks such as increased intracranial pressure, cardiopulmonary dysfunction, and aspiration pneumonia 10 – 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of head position (lying flat vs sitting up) as a non-pharmacological therapy for stroke has been widely investigated, [1][2][3][4] but the results remain inconclusive, which has led to ambiguous recommendations by current guidelines. [5][6][7] Compared with the sitting-up position, the supine or lying-flat position can increase blood flow and improve oxygenation, 1-3 8-10 but it may increase the risk of intracranial pressure, cardiopulmonary dysfunction and aspiration pneumonia.…”
Section: Introduction and Rationalementioning
confidence: 99%